Understanding the relationships between programme quality, psychological needs satisfaction, and mental well-being in competitive youth sport. Issue 2 (4th March 2021) - Bean, Corliss; McFadden, Taylor; Fortier, Michelle; Forneris, Tanya
Abstract : Youth sport programme structures and processes can directly influence participation outcomes, including mental health and well-being. Researchers have found that programme quality and basic needs satisfaction foster psychosocial outcomes; however, limited research has examined the mechanisms that facilitate mental health. The purpose of this study was to examine relationships between programme quality, basic needs satisfaction, and mental well-being in competitive youth sport. Youth ( N  = 160, 89 males, 71 females; M age  = 15.36, SD = 2.50) completed questionnaires at mid-season, with questions related to quality of their sport programming, and at programme end, with questions pertaining to basic needs satisfaction and mental well-being. Structural equation modelling was used to test the direct relationships between programme quality and mental well-being ( r  = .46, p  < .001; model 1) and between basic needs satisfaction and mental well-being ( r  = .63, p  < .001; model 2). Using several fit indices, results showed an adequate fit of both models to the data, suggesting that programme quality significantly predicted basic needs satisfaction and basic needs satisfaction significantly predicted mental well-being. Bootstrapping analysis was used to test if basic needs satisfaction mediated the relationship between programme quality and mental well-being. Results supported mediation, with a large effect ( k 2  = 0.28). The study findings help to emphasise the value of structuring youth sport programmes to satisfy basic needs, which may have positive implications on youth mental health. This is important because supporting mental well-being at an earlier age may facilitate mental health and well-being in adulthood.